RETRACTED ARTICLE: Emerging insights into the role of IL-1 inhibitors and colchicine for inflammation control in type 2 diabetes - Jianbin Guan; Haimiti Abudouaini; Kaiyuan Lin; Kaitan Yang (Diabetology & Metabolic Syndrome)
Abstract Type 2 diabetes mellitus (T2DM), a prevalent chronic metabolic disorder, is closely linked to persistent low-grade inflammation, significantly contributing to its development and progression. This review provides a comprehensive examination of the inflammatory mechanisms underlying T2DM, focusing on the role of the NLRP3 inflammasome and interleukin-1β (IL-1β) in mediating inflammatory responses. We discuss the therapeutic potential of IL-1 inhibitors and colchicine, highlighting their mechanisms in inhibiting the NLRP3 inflammasome and reducing IL-1β production. Recent studies indicate that these agents could effectively mitigate inflammation, offering promising avenues for the prevention and management of T2DM. By exploring the intricate connections between metabolic disturbances and chronic inflammation, this review underscores the need for novel anti-inflammatory strategies to address T2DM and its complications.